Alumina-Mediated π-Activation of Alkynes - Akhmetov, Vladimir; Feofanov, Mikhail; Sharapa, Dmitry; Amsharov, Konstantin (Journal of the American Chemical Society, 2021)
The ability to induce powerful atom-economic transformation of alkynes is the key feature of carbophilic π-Lewis acids such as gold- and platinum-based catalysts. The unique catalytic activity of these compounds in electrophilic activations of alkynes is explained through relativistic effects, enabling efficient orbital overlapping with π-systems. For this reason, it is believed that noble metals are indispensable components in the catalysis of such reactions. In this study, we report that thermally activated γ-Al2O3 activates enynes, diynes, and arene-ynes in a manner enabling reactions that were typically assigned to the softest π-Lewis acids, while some were known to be triggered exclusively by gold catalysts. We demonstrate the scope of these transformations and suggest a qualitative explanation of this phenomenon based on the Dewar-Chatt-Duncanson model confirmed by density functional theory calculations.
CRIS-Team Scopus Importer:2021-10-08

Alumina-promoted oxodefluorination - Akhmetov, Vladimir; Feofanov, Mikhail; Amsharov, Konstantin (RSC Advances, 2020)
A simple protocol for the clean preparation of heterocyclic compounds containing dibenzofuran's core via oxodefluorination of fluoroarenes on activated γ-Al2O3 is reported. Alumina can be considered as a reliable oxygen source enabling one-pot substitution of fluorine atoms and yielding benzoannulated furan derivatives. The corresponding C-F bond activation is selective towards less stable C-Br/C-I and occurs under metal- A nd solvent-free conditions.
CRIS-Team Scopus Importer:2020-03-31

Annulation Cascade of Aryl Alkynes Induced by Alumina-Mediated C-F Bond Activation - Feofanov, Mikhail; Akhmetov, Vladimir; Amsharov, Konstantin (physica status solidi (b), 2020)
Alumina-mediated C-F activation (AmCFA) is an established method to generate incipient phenyl cation (IPC) through polarization of C(aryl)-F bonds. Herein, it is reported that AmCFA can be used to induce intramolecular arylation of aryl alkynes containing one, two, and three triple bonds. During the reaction, a single formally eliminated hydrogen fluoride (HF) leads to the formation of two, three, and four C-C bonds, respectively. Thus, the transformation gives rapid access to π-extension and serves as an interesting example of solid-state rational domino annulation enabling the bottom-up construction of nanographenes.
CRIS-Team Scopus Importer:2020-08-21
Keywords: alkyne annulations; C-F bond activation; nanographenes

Catalyst-Free Synthesis of O-Heteroacenes by Ladderization of Fluorinated Oligophenylenes - Feofanov, Mikhail; Akhmetov, Vladimir; Takayama, Ryo; Amsharov, Konstantin (Angewandte Chemie International Edition, 2021)
A novel catalyst-free approach to benzoannulated oxygen-containing heterocycles from fluorinated oligophenylenes is reported. Unlike existing methods, the presented reaction does not require an oxygen-containing precursor and relies on an external oxygen source, potassium tert-butoxide, which serves as an O2− synthon. The radical nature of the reaction facilitates nucleophilic substitution even in the presence of strong electron-donating groups and enables de-tert-butylation required for the complete annulation. Also demonstrated is the applicability of the method to introduce five-, six-, and seven-membered rings containing oxygen, whereas multiple annulations also open up a short synthetic path to ladder-type O-heteroacenes and oligodibenzofurans.
CRIS-Team Scopus Importer:2021-03-05
Keywords: annulations; heterocycles; oligomers; radicals; reaction mechanisms

Effect of the Cove Region Geometry in Polycyclic Aromatic Hydrocarbons on Alumina-Assisted Cyclodehydrofluorination - Akhmetov, Vladimir; Amsharov, Konstantin (physica status solidi (b), 2019)
Despite conventional opinion on high inertness of aluminum oxide and exceptional stability of the carbon–fluorine bond, activated γ-alumina effectively polarizes the C–F bond. This process is known to implement effective C–C coupling in the cove region, leading to intramolecular annulation and formation of non-alternant polycyclic aromatic hydrocarbons (PAHs). Herein, the importance of the cove region geometry on annulation efficiency is shown. This is demonstrated using precursor 1 as a model, which allows investigation of the cove region's major feature, namely its helical geometry, and effect of its structure on the efficiency of intramolecular C–C bond formation. Herein, the synthesis of 1, its behavior on activated alumina, and reasoning for the observed outcomes are described.
CRIS-Team Scopus Importer:2019-08-27
Keywords: aluminum oxide; cyclodehydrofluorination; C–F bond activation; solid-state synthesis

Folding of fluorinated oligoarylenes into non-alternant PAHs with various topological shapes - Akhmetov, Vladimir; Foertsch, Andreas; Feofanov, Mikhail; Troyanov, Sergey; Amsharov, Konstantin (Organic Chemistry Frontiers, 2020)
An unprecedented [6]helicene's cavity closure indicating the possibility of introducing seven-membered rings via alumina-mediated C-F activation is shown. This finding, in combination with a directed quadruple annulation of fluorinated oligoarylenes, opens a short pathway to elusive non-alternant PAHs. Starting with one fluorinated block, we have synthesized through a two-step procedure three new representatives with helical-, bowl- and saddle-shapes. Additionally, the structure-property relationship in these new PAHs is explored via theoretical, optical, and X-ray crystallographic studies.
CRIS-Team WoS Importer:2020-06-16

Modular Approach to the Synthesis of Two-Dimensional Angular Fused Acenes - Feofanov, Mikhail; Akhmetov, Vladimir; Sharapa, Dmitry I.; Amsharov, Konstantin (Organic Letters, 2020)
Herein, we present a modular approach to pristine angularly fused planar acenes. The approach includes the Pd-catalyzed fusion of several building blocks and implements a dehydrative extension (DPEX) reaction as a key step enabling facile access to diverse two-dimensional acenes. The scope was demonstrated on nine examples with up to quantitative yield.
CRIS-Team Scopus Importer:2020-02-04

Oxidative Electrocyclization of Diradicaloids: C-C Bonds for Free or How to Use Biradical Character for π-Extension - Feofanov, Mikhail; Akhmetov, Vladimir; Sharapa, Dmitry I.; Amsharov, Konstantin (Organic Letters, 2020)
Herein, we show that biradical character and appropriate distribution of spin density can be used for synthetic purposes. We demonstrate the rational domino annulation that includes dehydrative π-extension (DPEX) as the initiation step and subsequent oxidative electrocyclizations (EC) promoted by favorable localization of the unpaired electrons enabling up to four C-C bonds formed during the reaction. Contradicting to the Woodward-Hoffmann rules, the reaction proceeds at room temperature, whereas termination occurs when biradical character vanishes.
CRIS-Team Scopus Importer:2020-07-10

Photocyclization of diarylethylenes with a boronate moiety: a useful synthetic tool to soluble PAH building blocks - Feofanov, Mikhail; Uka, Arber; Akhmetov, Vladimir; Amsharov, Konstantin (Photochemical & Photobiological Sciences, 2020)
The synthesis of ten ortho-fused PAHs bearing boronic pinacol ester groups (BPin) is reported. The products are obtained via modification of Mallory photocyclization in 45-99% yields. Among them are examples of highly strained molecules such as [4]helicene derivatives with BPin substituents in the cavity. The method allows double C-C coupling and tolerates more than one BPin functionality.
CRIS-Team Scopus Importer:2020-06-02

Planar π-extended cycloparaphenylenes featuring an all-armchair edge topology - Xiang, Feifei; Maisel, Sven; Beniwal, Sumit; Akhmetov, Vladimir; Ruppenstein, Cordula; Devarajulu, Mirunalini; Dörr, Andreas; Papaianina, Olena; Görling, Andreas; Amsharov, Konstantin; Maier, Sabine (Nature Chemistry, 2022)
The [n]cycloparaphenylenes ([n]CPPs)—npara-linked phenylenes that form a closed-loop—have attracted substantial attention due to their unique cyclic structure and highly effective para-conjugation leading to a myriad of fascinating electronic and optoelectronic properties. However, their strained topology prevents the π-extension of CPPs to convert them either into armchair nanobelts or planarized CPP macrocycles. Here we successfully tackle this long-standing challenge and present the bottom-up synthesis and characterization of atomically precise in-plane π-extended [12]CPP on Au(111) by low-temperature scanning probe microscopy and spectroscopy combined with density functional theory. The planar π-extended CPP is a nanographene with an all-armchair edge topology. The exclusive para-conjugation at the periphery yields delocalized electronic states and the planarization maximizes the overlap of p orbitals, which both reduce the bandgap compared to conventional CPPs. Calculations predict ring currents and global aromaticity in the doubly charged system. The intriguing planar ring topology and unique electronic properties make planar π-extended CPPs promising quantum materials. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-07-08

Quantitative Evaluation of Fullerene Separation by Liquid Chromatography - Süß, Sebastian; Michaud, Vanessa; Amsharov, Konstantin; Akhmetov, Vladimir; Kaspereit, Malte; Damm, Cornelia; Peukert, Wolfgang (Journal of Physical Chemistry C, 2019)
Although a huge number of facile synthesis methods for nanoparticles (NPs) do exist, the products usually exhibit a distribution in particle size and shape. Thus, a separation step needs to be applied to adjust the particle properties according to the needs of the later application. Chromatography is a potentially scalable separation method which is well-established for separating molecules and promising for classifying NPs by size. Herein, we lay the foundations of particle chromatography by studying the separation of a C-60/C-70 fullerene mixture as well-defined particle probes using a pyrene-functionalized silica stationary phase. C-60 fullerenes are perfect model particles as they are spherical, roughly 1 nm in diameter, interacting via van der Waals interactions only. First, we extract the Henry coefficients for C-60 and C-70 fullerenes from the elution behavior of the fullerene mixture. Using a particle-wall as well as particle-particle model for the van der Waals interaction potential, we determine the Hamaker constant of the stationary phase material from the measured Henry coefficients. Moreover, we investigate the concentration-dependent diffusion and mass transport in the column by quantitative evaluation of the flow rate dependent elution behavior of the fullerenes. Our study shows the huge potential of chromatography for the separation of nanoparticles and demonstrates the strength of physical-chemical concepts for the quantitative analysis and the prediction of nanoparticle classification.
CRIS-Team WoS Importer:2019-07-30

Solid-state construction of zigzag periphery via intramolecular C-H insertion induced by alumina-mediated C-F activation - Feofanov, Mikhail; Foertsch, Andreas; Amsharov, Konstantin; Akhmetov, Vladimir (Chemical Communications, 2021)
C-aryl-F bond activation has become an important and quickly developing method for construction of carbon-based materials. We report that alumina-mediated C-F bond activation (AmCFA) enables construction of PAHs with zigzag periphery. This method includes formal C-sp(3)-H activation and opens an avenue for generation of carbon-based nanomagnets directly on technologically relevant surfaces.
CRIS-Team WoS Importer:2021-11-12

Tailoring Diindenochrysene through Intramolecular Multi-Assemblies by C−F Bond Activation on Aluminum Oxide - Akhmetov, Vladimir; Feofanov, Mikhail; Troyanov, Sergey; Amsharov, Konstantin (Chemistry - A European Journal, 2019)
The unique nature of the alumina-mediated cyclodehydrofluorination gives the opportunity to execute the preprogrammed algorithm of the C−C couplings rationally built into a precursor. Such multi-assemblies facilitate the construction of the carbon-skeleton, superseding the conventional step-by-step by the one-pot intramolecular assembly. In this work, the feasibility of the alumina-mediated C−F bond activation approach for multi-assembly is demonstrated on the example of a fundamental bowl-shaped polycyclic aromatic hydrocarbon (diindenochrysene) through the formation of all “missing” C−C bonds at the last step. Beside valuable insights into the reaction mechanism and the design of the precursors, a facile pathway enabling the two-step synthesis of diindenochrysene was elaborated, in which five C−C bonds form in a single synthetic step. It is shown that the relative positions of fluorine atoms play a crucial role in the outcome of the assembly and that governing the substituent positions enables the design of effective precursor molecules “programmed” for the consecutive C−C bond formations. In general, these findings push the state of the field towards the facile synthesis of sophisticated bowl-shaped carbon-based nanostructures through multi-assembly of fluoroarenes.
CRIS-Team Scopus Importer:2019-05-17
Keywords: aromatization; buckybowls; C−C coupling; C−F activation; multi-assembly

Towards Nonalternant Nanographenes through Self-Promoted Intramolecular Indenoannulation Cascade by C−F Bond Activation - Akhmetov, Vladimir; Feofanov, Mikhail; Papaianina, Olena; Troyanov, Sergey; Amsharov, Konstantin (Chemistry - A European Journal, 2019)
Large polycyclic aromatic hydrocarbons (PAHs) containing pentagons represent an important class of compounds that are considered to be superior materials in future nano-electronic applications. From this perspective, the development of synthetic approaches to large PAHs and nanographenes (NGs) is a matter of great importance. In this context indenoannulation appears to be the most practical way to introduce pentagons into NGs. Here we report that alumina-mediated C−F bond activation is an attractive tool for the synthesis of non-alternant NGs bearing several pentagons. The unique nature of the reaction leads to a rather counter-intuitive outcome and allows considering each previous aryl–aryl coupling as a promoter of the following one, despite the continuous increase in the strain energy. Thus, the presented strategy combines both facile synthesis and significant yields for large nonalternant PAHs and NGs.
CRIS-Team Scopus Importer:2019-08-20
Keywords: aromatization; buckybowls; C−C coupling; C−F activation; indenoannulation

Transition-metal free synthesis of N-aryl carbazoles and their extended analogs - Feofanov, Mikhail; Akhmetov, Vladimir; Takayama, Ryo; Amsharov, Konstantin (Organic & Biomolecular Chemistry, 2021)
Herein, we describe a facile synthesis of N-arylated carbazoles via ladderization of fluorinated oligophenylenes. The reaction consists of two subsequent nucleophilic substitutions triggered by an electronic transfer from dimsyl anions. The reaction allows the effective one-pot formation of at least six C-N bonds with pronounced selectivity to the C-F bond placement.
CRIS-Team WoS Importer:2021-08-20

Unusual Fusion of -Fluorinated Benzophenones under McMurry Reaction Conditions - Akhmetov, Vladimir; Feofanov, Mikhail; Ioutsi, Vitaliy; Hampel, Frank; Amsharov, Konstantin (Chemistry - A European Journal, 2019)
By exposure of -fluorinated benzophenones to McMurry reaction conditions, we have observed the remarkable formation of 9,10-diphenylanthracene derivatives. This unexpected transformation necessitates the cleavage of the exceptionally stable aromatic C-F bond under mild McMurry conditions. In this work, the condensation of several related fluorinated benzo- and acetophenones has been investigated, which allow us to propose a domino-like fusion mechanism for this unusual transformation. The scope and limitations of the fluorine-promoted benzophenone fusion are subsequently discussed.
CRIS-Team WoS Importer:2019-03-01